SELF-REALIZATION OF PERSONALITY IN SPORTS IN MODERN CONTEXTS (Psychology Travelogs, 2024)
The article presents a theoretical exploration of the process of self-realization in sports activities. Self-realization is a complex and multifaceted subject for psychological research. The study examines and analyzes the self-realization of an individual in sports—as a method, process, and outcome of achieving sports mastery. This is contextualized within specific historical conditions of life activity, utilizing preparation tools aligned with the athlete's abilities and talents. It assumes that the individual consciously chooses the content, means, and methods of achieving goals, that hold personal significance and are acceptable within societal norms.The distinction between the social significance of self-realization and its personal importance for the individual explains the process of forming a personal value system. In characterizing the psychological regulators and factors of an individual’s self-realization, both the substantive and semantic content of values and their spatial and temporal characteristics are crucial.The need to investigate the issue of self-realization arises from the lack of methods and tools within specialist training programs that address practical tasks focused on the athlete's individuality.The most complete self-realization in sports, the integration of universal humanistic ideals and values into sports activities prevents the possibility of its use for inhumane purposes. The significance of this issue in the sphere of sports activities is determined by the need to improve the content and forms of psychological training of athletes.It is necessary to provide student-athletes with a meaningful, psychologically competent introduction to the meaning, purpose, and professionally significant values of sports activities, thereby expanding their understanding of the possibilities of self-realization in their chosen profession.
Keywords: self-realization; sports activities; athlete’s personality; professional self-determination